Analytical Study Of Applying Electronic Governance Program In Baghdad Tennis Confederation - Mohammed, Ismael; Mohammed, Tuqa (Journal of Physical Education, 2018)
Analytical Study Of Applying Electronic Governance Program In Baghdad Tennis ConfederationThe importance of the study lies in identifying the reality of the application of electronic governance in Tennis Federation as well as identifying the obstacles that prevented the implementation of this system. The research problem focused on asking the following questions: What is the reality of implementing e-governance in Tennis Federation? and What are the obstacles facing the implementation of electronic governance in Tennis Federation?The aim of the research was to identify the reality of the application of electronic governance in Tennis Federation, and to identify the obstacles that prevented its implementation. The sample of the research included (87) players, trainers and referees of this federation. The electronic governance measure was applied to the research sample. The data was collected and treated to conclude that the federation lacks the material and human resources, modern technologies and people with competence and experience in their field of specialization. Finally they recommended using electronic governance within the federation.